Answer:
(x + 4)(x - 4)
Step-by-step explanation:
There are actually quite a lot of pairs of binomials the disproves Eric's conclusion, but they all model after the same special product: a^2 - b^2.
The special product a^2 - b^2 can be factored into (a + b)(a - b) and for all real a and b, it will come out as a binomial.
Here is an example:
(x + 4)(x - 4)
We can use the distributive property to get:
x^2 - 4x + 4x - 16
which is the same as
x^2 - 16
This would disprove Eric's conclusion.
Well, you have to do it with the substitution method now it's not easy, it takes some time to get used to it. I'm not really sure how to explain it but if you go on Khan Academy it will show you how to do it.
Since both equations are equal to y you can just make them equal to each other, like this 3x + 7 = x - 9. From there isolate the varible x on one side so that the solution will be on the other side of the equation. I'll do the steps too for you.
3x + 7 = x - 9
2x + 7 = -9
2x = -16
x = -8
Hope this helps :)
Step-by-step explanation:
![{m}^{3} = {cm}^{3} = \div {10}^{6}](https://tex.z-dn.net/?f=%20%7Bm%7D%5E%7B3%7D%20%20%3D%20%20%7Bcm%7D%5E%7B3%7D%20%20%3D%20%20%5Cdiv%20%7B10%7D%5E%7B6%7D%20%20)
0.2m^3 = 0.0000002 cm^3